Social Inclusion and Financial Protection through Community Financing : Initial Results from Five Household Surveys - Jakab, Melitta; Preker, Alexander S.; Krishnan, Chitra; Schneider, Pia; Diop, François; Jütting, Johannes; Gumber, Anil; Ranson, Kent; Supakankunt, Siripeni (World Bank, Washington, DC, 2013)
This paper provides empirical evidence regarding the performance of community-based health care financing in terms of (a) social inclusion and (b) financial protection. Five non-standardized household surveys were analyzed from India (two samples), Senegal, Rwanda, and Thailand. Common methodology was applied to the five data sets. Logistic regression was used to estimate the determinants of enrolling in a community financing scheme. A two-part model was used to assess the determinants of financial protection: part one used logistic regression to estimate the determinants of the likelihood of visiting a health care provider; part two used ordinary least-squares regression to estimate the determinants of out-of-pocket payments. The research finds: (a) Social inclusion. The findings suggest that community financing can be inclusive of the poorest even in the most economically deprived context. Nevertheless, this targeting outcome is not automatically attributable to the involvement of the community; rather it depends on key design and implementation characteristics of the schemes. (b) Financial protection. Community financing reduces financial barriers to health care as demonstrated by higher utilization and simultaneously lower out-of-pocket expenditure of scheme members controlling for a range of socioeconomic variables. The paper concludes: (a) Social inclusion. Design and implementation characteristics of community financing schemes matter to achieve good targeting outcome-community involvement alone does not guarantee social inclusion. Further research is needed to delineate which design and implementation characteristics allow better inclusion of the poor. (b) Financial protection. Prepayment and risk sharing, even on a small scale, reduce financial access barriers.